Respuesta :

Answer:

The option A) -4-3i is correct

Therefore the simplified given expression is (-1-6i)+(-3+3i)=-4-3i

Step-by-step explanation:

Given that the expression is (-1-6i)+(-3+3i)

To simplify the given expression as below :

(-1-6i)+(-3+3i)=-1-6i-3+3i

=(-1-3)+(-6i+3i) ( combining the real parts and imaginary parts separately and adding the like terms )

=-4+(-3i)

=-4-3i

(-1-6i)+(-3+3i)=-4-3i

Therefore the simplified given expression is (-1-6i)+(-3+3i)=-4-3i

Therefore the option A) -4-3i is correct